TRUST - PERILAKU IMITASI DALAM MEMBANGUN EKONOMI KELUARGA MISKIN DI KECAMATAN BIBOKI TANPAH KABUPATEN TIMOR TENGAH UTARA PROVINSI NUSA TENGGARA TIMUR - Ngginak, Adrianus Aluman (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
In various human activities, trust and imitation are always inseparable. Likewise, activities related to the family economy, especially in rural communities, are often triggered by the habit of imitating what the initiator does. Previous studies have looked at the follower-leader relationship and show that followers will imitate the leader if their integrity is not violated. This study focuses more on trust, imitators and initiators. Therefore, the questions that should be answered are why and how do individual family processes as imitators always imitate the actions, attitudes of initiators or initiators in the countryside. The findings show that the imitator always imitates the actions of the initiator because 1) it benefits the imitator. 2) The imitator always imitates both positive and negative actions. 3) The imitator can use parties who are experienced in negative actions but benefit groups or individuals. 4) Using social media as a guide.